An Attempt to Formulate a Preliminary Definition of the Validity of Norms - Patryas, Wojciech (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2020)
The aim of the study is to formulate a preliminary defnition of the validity of norms using idealization method for this purpose. The author proposes a preliminary definition of the validity of norms and compares it with the conception of such a definition put forward by Leszek Nowak in Interpretacja prawnicza. Studium z metodologii prawoznawstwa.